2016
DOI: 10.1177/0306624x16630543
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Living Group Climate, Aggression, and Callous-Unemotional Traits in Delinquent Boys in Detention

Abstract: Aggression and callous-unemotional (CU) traits are common problems in incarcerated delinquent youth. The present study was conducted to examine whether living group climate was associated with aggression and CU traits in late adolescent male offenders ( N = 156) in a German youth prison. A structural equation model was fitted to the data and showed associations between repression and reactive aggression and CU traits, but no associations between an open and supportive living group climate and aggression and CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 77 publications
3
25
3
Order By: Relevance
“…These findings support the hypothesis of an influence of the living group climate, with an emphasis on its positive characteristics, in contrast with the historically emphasized negative characteristics described in the deprivational model (Harer & Steffensmeier, 1996). More recently, a study by Heynen et al (2016b), in a German youth prison for adolescent male offenders, shows a significant positive association between self-reported reactive aggression and the perception of repression. No associations with a living group climate characterized by support, growth, and a positive atmosphere were found.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…These findings support the hypothesis of an influence of the living group climate, with an emphasis on its positive characteristics, in contrast with the historically emphasized negative characteristics described in the deprivational model (Harer & Steffensmeier, 1996). More recently, a study by Heynen et al (2016b), in a German youth prison for adolescent male offenders, shows a significant positive association between self-reported reactive aggression and the perception of repression. No associations with a living group climate characterized by support, growth, and a positive atmosphere were found.…”
supporting
confidence: 78%
“…Based on two earlier described studies in a Dutch youth correctional facility (van der Helm et al, 2012b) and in a German youth prison (Heynen et al, 2016b), we hypothesized to find an association between the number of aggressive incidents and support and possibilities for growth experienced by the adolescents in the forensic treatment unit.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on children's perceived group climate, defined as the quality of the social and physical environment provision that is sufficient and necessary for physical and mental well-being (e.g., perceived support from staff) (Strijbosch, Van der Helm, Stams, & Wissink, 2016;Ten Brummelaar et al, 2017). Results showed that positively perceived group climate was associated with positive outcomes of the children such as better coping, more empathy, and less aggression (Heynen, van der Helm, Cima, Stams, & Korebrits, 2017;van der Helm, Klapwijk, Stams, & van der Laan, 2009). However, it is possible that children with children with better psychological and social adaptation rating this group climate more positively, cofounding this association.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has also been reported that a positive living group climate is positively associated with increased cognitive empathy of the clients (). In mental healthcare services, an open and positive living group climate is reported to contribute to fewer incidents of aggression (De Decker et al, ; Heynen, Van der Helm, Cima, Stams, & Korebrits, b; Ros, Van der Helm, Wissink, Schaftenaar, & Stams, ). Author's own (, p. 120) argued that an open living group climate should be a main concern for staff and workers and should be regularly monitored and improved.…”
Section: Introductionmentioning
confidence: 99%